Analysis of M4 Transmembrane Segments in NMDA Receptor Function: A Negative Allosteric Modulatory Site at the GluN1 M4 is Determining the Efficiency of Neurosteroid Modulation - Kai Langer; Adriana Müller-Längle; Jannik Wempe; Bodo Laube; Bodo Laube (Frontiers Media S.A., 2021)
Ionotropic glutamate receptors (iGluRs) are tetrameric ligand-gated ion channels that play a crucial role in excitatory synaptic transmission in the central nervous system. Each subunit contributes with three helical transmembrane segments (M1, M3, and M4) and a pore loop (M2) to form the channel pore. Recent studies suggest that the architecture of all eukaryotic iGluRs derives from a common prokaryotic ancestral receptor that lacks M4 and consists only of transmembrane segments M1 and M3. Although significant contribution has emerged in the last years, the role of this additionally evolved transmembrane segment in iGluR assembly and function remains unclear. Here, we have investigated how deletions and mutations of M4 in members of the NMDA receptor (NMDAR) subfamily, the conventional heteromeric GluN1/GluN2 and glycine-gated GluN1/GluN3 NMDARs, affect expression and function in Xenopus oocytes. We show that deletion of M4 in the GluN1, GluN2A, or GluN3A subunit, despite retained receptor assembly and cell surface expression, results in nonfunctional membrane receptors. Coexpression of the corresponding M4 as an isolated peptide in M4-deleted receptors rescued receptor function of GluN1/GluN2A NMDARs without altering the apparent affinity of glutamate or glycine. Electrophysiological analyses of agonist-induced receptor function and its modulation by the neurosteroid pregnenolone sulfate (PS) at mutations of the GluN1-M4/GluN2/3-transmembrane interfaces indicate a crucial role of position M813 in M4 of GluN1 for functional coupling to the core receptor and the negative modulatory effects of PS. Substitution of residues and insertion of interhelical disulfide bridges confirmed interhelical interactions of positions in M4 of GluN1 with residues of transmembrane segments of neighboring subunits. Our results show that although M4s in NMDARs are not important for receptor assembly and surface expression, the residues at the subunit interface are substantially involved in M4 recognition of the core receptor and regulation of PS efficacy. Because mutations in the M4 of GluN1 specifically resulted in loss of PS-induced inhibition of GluN1/GluN2A and GluN1/GluN3A NMDAR currents, our results point to distinct roles of M4s in NMDAR modulation and highlight the importance of the evolutionarily newly evolved M4 for selective in vivo modulation of glutamate- and glycine-activated NMDARs by steroids.